NEGOSIASI MUSIKAL DAN SOSIO-KULTURAL PADA KESENIAN GANJURAN DI PURA WISNU SAKTI KLATEN - Supriyadi; Setiyono, Budi (Institut Seni Indonesia (ISI) Surakarta, 2024)
Ganjuran is a type of music that is a mixture of two types of music, namely Jathilan and Baleganjur music. This assimilation began with an identity polemic between Javanese and Balinese musicality which was felt by most Hindus in Klaten. The polemic turned out to be prolonged, until finally Pemuda Pura Wisnu Sakti offered a solution to blend the two musicalities. In carrying out assimilation, Pemuda Pura Wisnu Sakti apparently carried out musical and socio-cultural negotiations with various elements to find an ideal. Next, to describe the negotiations, Yuniawan’s negotiation strategy theory was used. The method used in this research is qualitative, descriptive analytic in nature. As a result, it was identified that there were musical negotiations which included instruments and playing patterns as well as socio-cultural negotiations which included identity, satisfaction of players and listeners, and suitability of musicality with worship. These results show that music can be used as a tool to maintain identity in a friendly way.